Adaptive compensation control for attitude adjustment of quad-rotor unmanned aerial vehicle. (July 2017) - Song, Zhankui; Sun, Kaibiao
Abstract: A compensation control strategy based on adaptive back-stepping technique is presented to address the problem of attitude adjustment for a quad-rotor unmanned aerial vehicle (QR- UAV) with inertia parameter uncertainties, the limited airflow disturbance and the partial loss of rotation speed effectiveness. In the design process of control system, adaptive estimation technique is introduced into the closed loop system in order to compensate the lumped disturbance term. More specifically, the designed controller utilizes "prescribed performance bounds" method, and therefore guarantees the transient performance of tracking errors, even in the presence of the lumped disturbance. Adaptive compensation algorithms under the proposed closed loop system structure are derived in the sense of Lyapunov stability analysis such that the attitude tracking error converge to a small neighborhood of equilibrium point. Finally, the simulation results demonstrate the effectiveness of the proposed controller. Highlights: A group of updating laws using adaptive mechanism are introduced into the closed loop system. The closed loop control system is designed with prescribed performance bounds. The proposed adaptive control schemes are an on-line compensation technique.